2009
DOI: 10.1111/j.1758-5740.2009.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial Impingement: Is there Correlation between Symptoms, Arthroscopic Findings and Outcomes?

Abstract: Background To determine whether a correlation exists between the clinical symptoms and signs of impingement, and the severity of the lesions seen at bursoscopy. Methods Fifty-five patients who underwent arthroscopic subacromial decompression were analyzed. Pre-operatively patients completed an assessment form consisting of visual analogue pain score, and shoulder satisfaction. The degree of clinical impingement was also recorded. At arthroscopy impingement was classified according to the Copeland-Levy classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Yet research into subacromial decompression surgery in which the subacromial bursa is excised has shown that outcomes of this procedure, whether done with or without acromioplasty, are no different (Budoff et al, 2005;Henkus et al, 2009). This would support the notion that the morphology of the acromion has no bearing on subacromial impingement syndrome and this view is supported by numerous authors (Gill et al, 2002;Snow et al, 2009). …”
Section: Anatomical/osseous Factorssupporting
confidence: 70%
“…Yet research into subacromial decompression surgery in which the subacromial bursa is excised has shown that outcomes of this procedure, whether done with or without acromioplasty, are no different (Budoff et al, 2005;Henkus et al, 2009). This would support the notion that the morphology of the acromion has no bearing on subacromial impingement syndrome and this view is supported by numerous authors (Gill et al, 2002;Snow et al, 2009). …”
Section: Anatomical/osseous Factorssupporting
confidence: 70%
“…At the 6 month follow-up no significant correlation between pain and satisfaction and the severity of structural pathology was identified. 42 Confirming this, after a study of 523 people undergoing arthroscopic or open shoulder surgery, Gill et al 43 reported no significant association between acromial shape and rotator cuff pathology in people over 50 years of age (n5192). A highly significant correlation between age and rotator cuff pathology existed and the researchers argued that a Type III hooked acromial represents a degenerative process rather than a morphological variation as described by Bigliani.…”
Section: Acromial Shapementioning
confidence: 96%
“…As discussed earlier there is a poor correlation between acromial radiological changes and symptoms. [41][42][43] In a study of 96 people without shoulder symptoms 28% or those aged between 40 and 60 years and 54% of those aged above 60 years had MRI evidence of a partial or full thickness rotator cuff tear. 114 Milgrom et al 115 reported in a study of 90 people (age range 30 to 99 without shoulder symptoms) that the incidence of full thickness rotator cuff tears identified by ultrasound increased with advancing age and that after the 5th decade approximately 50% of people had asymptomatic full thickness tears that did not affect function.…”
Section: The Subacromial Bursamentioning
confidence: 99%
See 1 more Smart Citation
“…Bigliani et al, (1986) described three distinct acromial shapes (flat, curved and hooked) attributing the differences to morphological variations and argued those with a Type III or hooked acromion would be more likely to experience subacromial pain symptoms and suffer a RC tear. Definitive causation has not been established and there appears to be a poor correlation between acromial shape and symptoms (Gill et al , 2002, Snow et al , 2009, Worland et al , 2003 further challenging the acromial model of RC tendinopathy. In addition, if the acromion is the cause for impingement and this eventuates in RC tears, a SAD should halt this process.…”
Section: Aetiologymentioning
confidence: 99%